Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(4\sqrt{\frac{2}{9}}+\sqrt{2}+\sqrt{\frac{1}{18}}\)
\(=\frac{8\sqrt{2}}{6}+\frac{6\sqrt{2}}{6}+\frac{\sqrt{2}}{6}\)
\(=\frac{15\sqrt{2}}{6}=\frac{5\sqrt{2}}{2}\)
b) \(\frac{1}{\sqrt{3}-1}-\frac{1}{\sqrt{3}+1}\)
\(=\frac{\sqrt{3}+1}{3-1}-\frac{\sqrt{3}-1}{3-1}\)
\(=\frac{\sqrt{3}+1-\sqrt{3}+1}{2}=1\)
\(\frac{4}{\sqrt{3}+1}-\frac{5}{\sqrt{3}-2}+\frac{6}{\sqrt{3}-3}\)
\(=\frac{4\left(\sqrt{3}-1\right)}{\left(\sqrt{3}+1\right)\left(\sqrt{3}-1\right)}-\frac{5\left(\sqrt{3}+2\right)}{\left(\sqrt{3}-2\right)\left(\sqrt{3}+2\right)}+\frac{6\left(\sqrt{3}+3\right)}{\left(\sqrt{3}+3\right)\left(\sqrt{3}-3\right)}\)
\(=\frac{4\sqrt{3}-4}{2}-\frac{5\sqrt{3}+10}{-1}+\frac{6\sqrt{3}+18}{3-9}\)
\(=2\sqrt{3}-2+5\sqrt{3}+10-\sqrt{3}-3\)
\(=6\sqrt{3}+5\)
a/ \(\frac{1}{2-\sqrt{3}}+\frac{3+\sqrt{3}}{\sqrt{3}}-\frac{4}{\sqrt{3}-1}\)
\(=2+\sqrt{3}+\sqrt{3}+1-2\sqrt{3}-2\)
\(=1\)
b/ \(\sqrt{3x+40}-4=x\)
\(\sqrt{3x+40}=x+4\)
Điều kiện: \(\hept{\begin{cases}3x+40\ge0\\x+4\ge0\end{cases}}\)
\(\Leftrightarrow\hept{\begin{cases}x\ge-\frac{40}{3}\\x\ge-4\end{cases}}\)
\(\Leftrightarrow x\ge-\frac{40}{3}\)
Ta có: \(3x+40=x^2+8x+16\)
\(\Leftrightarrow x^2+5x-24=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=-8\left(l\right)\\x=3\end{cases}}\)
a. Ta có \(\frac{1}{2-\sqrt{3}}+\frac{3\sqrt{3}}{\sqrt{3}}-\frac{4}{\sqrt{3}-1}=\frac{2+\sqrt{3}}{\left(2+\sqrt{3}\right)\left(2-\sqrt{3}\right)}+3-\frac{4\left(\sqrt{3}+1\right)}{\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)}\)
\(=\frac{2+\sqrt{3}}{4-3}+3-\frac{4\left(\sqrt{3}+1\right)}{3-1}=2+\sqrt{3}+3-2\sqrt{3}-2=3-\sqrt{3}\)
b. \(\sqrt{3x+40}-4=x\)
ĐK \(3x+40\ge0\Leftrightarrow x\ge-\frac{40}{3}\)
\(\Leftrightarrow\sqrt{3x+40}=x+4\)\(\Leftrightarrow\hept{\begin{cases}x\ge-4\\3x+40=x^2+8x+16\end{cases}\Leftrightarrow\hept{\begin{cases}x\ge-4\\x^2+5x-24=0\end{cases}}}\)
\(\Leftrightarrow\hept{\begin{cases}x\ge-4\\\left(x+8\right)\left(x-3\right)=0\end{cases}\Leftrightarrow\hept{\begin{cases}x\ge-4\\x=-8;x=3\end{cases}}}\Leftrightarrow x=3\left(tm\right)\)
Vậy x=3
a, = \(\frac{\sqrt{7}-5}{2}-\frac{2\left(3-\sqrt{7}\right)}{4}+\frac{6\left(\sqrt{7}+2\right)}{\left(\sqrt{7}-2\right)\left(\sqrt{7}+2\right)}-\frac{5\left(4-\sqrt{7}\right)}{\left(4-\sqrt{7}\right)\left(4+\sqrt{7}\right)}\)
\(\frac{1}{\sqrt{3}-1}-\frac{1}{2}=\frac{\sqrt{3}+1}{\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)}-\frac{1}{2}\)
\(=\frac{\sqrt{3}+1}{3-1}-\frac{1}{2}=\frac{\sqrt{3}+1}{2}-\frac{1}{2}\)
\(=\frac{\sqrt{3}+1-1}{2}=\frac{\sqrt{3}}{2}\)
\(A=\frac{1}{\sqrt{3}-1}-\frac{1}{2}\)
\(=\frac{1\left(\sqrt{3}+1\right)}{\left(\sqrt{3}-1\right)\left(\sqrt{3}+1\right)}-\frac{1}{2}\)
\(=\frac{\sqrt{3}+1}{\left(\sqrt{3}\right)^2-1^2}-\frac{1}{2}\)
\(=\frac{\sqrt{3}+1}{2}-\frac{1}{2}\)
\(=\frac{\sqrt{3}}{2}\)